Tocilizumab in rheumatoid arthritis‐associated peripheral ulcerative keratitis: A 1‐year follow‐up case report. Issue 1 (27th January 2022) - Huang, Jia; Chen, Zhen; Zhao, Like; Cheng, Yongjing; Gao, Ming; Huang, Cibo; Wang, Zheng; Wang, Fang
Abstract: Clinical case: We report a case of rheumatoid arthritis‐associated peripheral ulcerative keratitis (PUK) successfully treated with tocilizumab. Despite being treated with systemic corticosteroids and several disease‐modifying antirheumatic drugs, evern though received corneal transplantation, the patient was still going to lose her sight. Tocilizumab resulted in a good response with control of her systemic illness and preventing the progress of corneal lesions. Discussion: Tocilizumab may be an additional tool for the patients with rheumatoid arthritis associated PUK that is refractory to other drugs. Abstract : (A) An invasive ulcer presented in nasal limbus with perforation and iris prolapse at 9 o'clock in the right eye of a 64‐year‐old female with rheumatoid arthritis. (B) Seven months after the treatment with tocilizumab. Corneal pannus completely covers the ulcer surface. The central depth of the anterior chamber was 4ct, anterior synechia, normal fundus. Key points: Peripheral ulcerative keratitis is a rare complication in patients with rheumatoid arthritis and it may cause a marked decrease of visual acuity or the loss of an eye. Tocilizumab may be an additional tool for patients with rheumatoid arthritis‐associated peripheral ulcerative keratitis that is refractory to other drugs.